2022
DOI: 10.1029/2022gl100505
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Missing Snowmelt Following Drought

Abstract: Water management in snowy mountainous regions hinges on forecasting snowmelt runoff. However, droughts are altering snowpack‐runoff relationships with ongoing debate about the driving mechanisms. For example, in 2021 in California, less than half of predicted streamflow arrived. Mechanisms proposed for this “missing” streamflow included changes in evapotranspiration (ET), rainfall, and subsurface moisture conditions. Here, we demonstrate that ET in drought years generates dry subsurface conditions that reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…The summer of 2021 provided a good example of multiple dry years in a row causing exceptionally low flows due to an accumulated deficit in subsurface water storage (Lapides et al, 2022). Water Year (WY) 2021 (denoted with an X in Figure 5) had the lowest Qmin in our study period for Sagehen and Merced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The summer of 2021 provided a good example of multiple dry years in a row causing exceptionally low flows due to an accumulated deficit in subsurface water storage (Lapides et al, 2022). Water Year (WY) 2021 (denoted with an X in Figure 5) had the lowest Qmin in our study period for Sagehen and Merced.…”
Section: Discussionmentioning
confidence: 99%
“…The summer of 2021 provided a good example of multiple dry years in a row causing exceptionally low flows due to an accumulated deficit in subsurface water storage (Lapides et al, 2022). Water Year Hatchett, 2023).…”
Section: Importance Of Multi-year Droughtsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, storage capacity calculated via deficit‐style approaches has many theoretical and pragmatic advantages. S R results in improved hydrological model performance when used as an input parameter (Lapides et al, 2023; Wang‐Erlandsson et al., 2016) and can explain continental‐scale patterns in water partitioning (Cheng et al., 2022) and storage dynamics (Trautmann et al., 2022); deficit calculations have also proven essential in the accurate prediction of snowmelt contributions to streamflow following droughts (Lapides et al., 2022). Importantly, deficit‐calculated S R does not require a priori assumptions regarding porosity or rooting profiles, and distributed hydrologic flux datasets make it feasible to estimate S R at large spatial scales in cloud‐based analysis platforms like Google Earth Engine.…”
Section: Introductionmentioning
confidence: 99%
“…However, rainfall in winter and the following warm season (April-September) can make nontrivial contributions to summer streamflow by replenishing soil moisture, a mechanism that generally has received less attention than snowmelt. For example, Lapides et al (2022) found that warm season runoff generation is strongly tied to root-zone water storage deficits, which must be replenished by snowmelt or rainfall before substantial runoff occur. Moreover, Cooper et al (2018) found a larger percentage change of summer low flows per percentage change of winter precipitation for rain-dominated catchments as compared with snow-dominated catchments in maritime WUS mountains.…”
mentioning
confidence: 99%